Supervising students in a complex nursing practice- a focus group study in Norway - Ann-Chatrin Leonardsen; Siri Brynhildsen; Mette Tindvik Hansen; Vigdis Abrahamsen Grøndahl (BMC, 2021)
Abstract Background The supervisory role of registered nurses and intellectual disability nurses will be even more essential in the future, to support the education of competent newly graduated candidates. To our knowledge few studies have explored nursing student supervisors' perspectives on supervision across primary- and hospital healthcare services and also across nurse educational programs. The aim of the current study was to investigate supervisors' perspectives on supervising from different clinical settings, and across registered nurses' and intellectual disability nurses' clinical practice. Methods The study had an exploratory and descriptive design. The study was conducted within one university college catchment area in Southeastern-Norway. Eight focous group interviews were conducted in primary healthcare (n = 4) and hospital (n = 4) wards. A total of 31 registered nurses and three intellectual disability nurses participated. Hsieh and Shannon's conventional content analysis was used to analyze the data. Results Participants across primary- and hospital healthcare agreed that clinical practice was complex, and required that students gained competence in both technical and non-technical skills. Moreover, needed skills were described both as general and arena specific, and as both basic and advanced. Participants perceived that technical and non-technical skills together, ideally should lead to students being able to «see the person» behind the patient. Conclusions Supervisors emphasized the challenges of supervising students in a complex nursing practice. Students should gain both procedural competence and an ability to provide person-centred care, and this challenged the supervisors' own competence. Our findings indicate a need to support supervisors, to enable them to meet these challenges.